Development of Supply Chain Risks Interrelationships Model using Interpretive Structural Modeling and Analytical Network Process - Chatarina Dian Indrawati; Putu Dana Karningsih; Iwan Vanany (IPTEK Journal of Proceedings Series, 2014)
Globalization and vast changing of business nature nowadays makes interdependence between organizations who shares the same supply network is becoming stronger.  Any risk that occurs in one point of a supply chain could affect to the whole network.  As a result, risk in supply chain is getting more complex and unpredictable. Since any kind of risk could potentially impede or even stop business activities of the whole supply chain therefore managing supply chain risk is essential. Moreover, to handle supply chain risk properly, the interrelationships between these risks should be identified. However, there is only few study which cover interrelationships between supply chain risks. This research is aiming to provide a proposed model of a supply chain interrelation risks based on case study in an petrochemical industry.   Interpretive Approach Structural Modeling is utilized to develop the relationships between risks while weight determination for risk relationship is conducted using Analytical Network Process.  The case study of this research identifies that there are 14 supply chain risks which are grouped as driver, dependent, autonomous and linkage. The weight of risk interrelations are then considered when quantify each risk.  Calculation of risk priority number is not only taking into account its own probability and consequence but also the probability and weight of affected risk.